1998
DOI: 10.1002/(sici)1096-9896(199803)184:3<240::aid-path20>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

FHIT andp53 gene abnormalities in bronchioloalveolar carcinomas. Correlations with clinicopathological data and K-ras mutations

Abstract: Bronchioloalveolar carcinoma (BAC) is a particular type of adenocarcinoma of the lung which accounts for up to 9 per cent of pulmonary malignancies. The aetiology and pathogenesis of this unique neoplastic disease are still unclear. Three histological subtypes of BAC have been recognized: mucinous, non‐mucinous, and sclerosing. Of these, mucinous and sclerosing BAC have a worse prognosis than non‐mucinous tumours. The different morphological patterns and clinical outcomes of the subtypes of BAC suggest differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
3
32
1
Order By: Relevance
“…The reported frequency of LOH at FHIT gene in NSCLC is between 20 and 70% of cases. 5,11,[17][18][19][20][21][22][23][24] Our results are similar to the highest frequency, with LOH in one or more microsatellites in 67.8% of 96 informative tumors. The differences between all series probably could be explained by the different markers used and the method of detection and evaluation of LOH.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The reported frequency of LOH at FHIT gene in NSCLC is between 20 and 70% of cases. 5,11,[17][18][19][20][21][22][23][24] Our results are similar to the highest frequency, with LOH in one or more microsatellites in 67.8% of 96 informative tumors. The differences between all series probably could be explained by the different markers used and the method of detection and evaluation of LOH.…”
Section: Discussionsupporting
confidence: 81%
“…3 Frequent allelic losses and homozygous deletions, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] as well as the loss of heterozygosity (LOH) in microsatellites located at FHIT gene 5,11,12,[17][18][19][20][21][22][23][24] have been described at the FHIT locus in several human solid tumors arising from epithelial cells, including lung cancer.…”
mentioning
confidence: 99%
“…In agreement with previous studies (Burke et al, 1998;Marchetti et al, 1998;Tomizawa et al, 1998;Geradts et al, 2000), allelic deletion of the FHIT locus did not correlate with sex, age, staging, lymph node metastasis and survival. Thus, our results are consistent with the role of FHIT abnormalities at a relatively early stage of pulmonary neoplasia, rather than in the metastatic progression of invasive lung cancers.…”
Section: Discussionsupporting
confidence: 92%
“…It was previously indicated that the genetic changes at the FHIT locus may be correlated with p53 mutations (Burke et al, 1998;Marchetti et al, 1998;Chang et al, 2003), while other investigators found no statistically significant correlation between FHIT and p53 abnormalities in NSCLCs (Nelson et al, 1998;Geradts et al, 2000). By examining the FHIT/ p53 profiles, we noticed that the nine cases with synergistic effect of LOH at FHIT locus and p53 overexpression included six squamous cell carcinomas and three adenocarcinomas.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation